2017
DOI: 10.1186/s12877-017-0496-2
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional determinants of frailty in older adults: A systematic review

Abstract: BackgroundFrailty is a geriatric syndrome that affects multiple domains of human functioning. A variety of problems contributes to the development of this syndrome; poor nutritional status is an important determinant of this condition. The purpose of this systematic review was to examine recent evidence regarding the association between nutritional status and frailty syndrome in older adults.MethodsPubMed, Web of Science, and Scopus electronic databases were searched using specific key words, for observational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
324
2
20

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(359 citation statements)
references
References 68 publications
13
324
2
20
Order By: Relevance
“…19,24 The findings of the current analysis are generally in line with these studies. Others have argued that chewing inability, mainly resulting from inadequate dentition, negatively impacts nutritional intake.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…19,24 The findings of the current analysis are generally in line with these studies. Others have argued that chewing inability, mainly resulting from inadequate dentition, negatively impacts nutritional intake.…”
Section: Discussionsupporting
confidence: 88%
“…Inadequate intake of nutrients related to frailty 19 was calculated according to the values of Recommended Dietary Intakes produced by the US Food and Drug Administration. Inadequate intake of nutrients related to frailty 19 was calculated according to the values of Recommended Dietary Intakes produced by the US Food and Drug Administration.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…There is growing evidence that inadequate nutrition is a determining factor in the development of frailty among older adults, both in terms of the quantity of calories consumed and the quality of nutrients taken 1. Frailty leads to reduced quality of life, loss of function and independence, and increased morbidity and mortality 2.…”
Section: Contextmentioning
confidence: 99%
“…26 These include amount of protein intake, 27-31 distribution of protein intake, 31 intake of specific micronutrients, 27,32-34 quality of diet (intake diversity) 35,36 and anti-oxidant capacity of the diet. In a systematic review, Lorenzo-López identified several nutritional determinants of frailty.…”
Section: Explanationmentioning
confidence: 99%